Inactivation of candida albicans by cold atmospheric pressure plasma jet - Kostov, Konstantin Georgiev [UNESP]; Borges, Aline Chiodi [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Nishime, Thalita Mayumi Castaldelli [UNESP]; Prysiazhnyi, Vadym [UNESP]; Honda, Roberto Yzumi [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2015)
Nonthermal atmospheric pressure plasma jets (APPJs) are characterized by very reactive chemistry without the need of elevated temperatures. Also, plasma jets are capable of producing cold plasma plumes that are not spatially confined by electrodes, which makes them very attractive for biomedical applications. In this paper, we investigate the antimicrobial efficiency of a simple plasma jet device operating with pure He as working gas. The device was driven by an ac power supply operated at 31.0 kHz, 13.0 kV amplitude with mean power around 1.8 W. The jet was directed perpendicularly on a standard Petri dish (O90 mm x 15 mm) filled with agar. The jet fungicidal efficiency was tested against Candida albicans (reference strains SC 5314 and ATCC 18804) and five clinical isolates from previously obtained denture stomatitis lesions. In this paper, the effects of treatment time and distance to the target were evaluated. In most treatments the samples did not have direct contact with the plasma plume; therefore, the reactive oxygen species produced by interaction between the plasma jet and ambient air were the principal inactivate agent.
Keywords: Candida albicans (C. albicans); Cold atmospheric plasma; Decontamination; Plasma jet